Ubuntu, koinonia and diakonia, a way to reconciliation in South Africa? - Gert Breed; Kwena Semenya (HTS Teologiese Studies/Theological Studies, 2015)
This article seeks to contribute to the process of reconciliation in South Africa. This is achieved by firstly exploring the meaning of ubuntu as a common culture or religion under a large percentage of South Africa’s people over the borders of language and other cultural values. In the second part of the article two concepts that play a major role in Christianity are explored, namely koinonia and diakonia. Again a large percentage of South Africans believe that the Bible is the Word of God in which the right way of living is described. A comparison is made between the core values of ubuntu and the way of living that emerges from the use of the two concepts of koinonia and diakonia in the New Testament. A way that can contribute to reconciliation is suggested from this comparison.